Morphological analysis of corn xerogel and its shape shifting in water. (October 2022) - Jaspin, S.; Anbarasan, R.; Dharini, M.; Mahendran, R.
Abstract: This research aims to develop cereal-based dried polymer gel (xerogel), investigate the use of these products as two-dimensional food paradigms that can be morphed into 3D forms, and quantify their hydrostimulated nature. Corn hydrogel (5 g/100 mL) was dried using a sessile drop drying process to obtain 2D flat corn xerogel. The upper and bottom portion of corn polymer xerogel was characterized as non-porous and porous nature. The FTIR spectroscopy discovered that the chemical nature of xerogel was not changed significantly from that of corn flour. Non-thermal plasma-treated corn polymer xerogel programmed into different 3D shapes like a spiral, and tubular through water stimuli (30 s). Corn xerogel self-bends due to its anisotropic nature. In this study, angle, height, the curve of bending are measured as indicators of shape change. Using hydro-stimulated shape changes, this paper discusses a new technology for designing attractive pasta made of 2D corn polymer xerogel. Graphical abstract: Image 1 Highlights: Plasma induced corn xerogel resulted good adhesion properties. Characterization of corn xerogel reveals dense top and porous bottom surfaces. Corn xerogel with ethyl cellulose coating triggered 3D shape change in water.